2009
DOI: 10.1093/humrep/dep366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inter- and intra-cycle variability of anti-Mullerian hormone and antral follicle counts

Abstract: Serum AMH demonstrated less individual intra- and inter-cycle variation than AFCs and may therefore be considered a more reliable and robust means of assessing ovarian reserve in subfertile women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
197
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(222 citation statements)
references
References 41 publications
10
197
1
14
Order By: Relevance
“…van Disseldorp et al [19] compared the AFC with the AMH as to both their inter-cycle variability across four subsequent cycles and their stability across a full cycle in 77 women undergoing intrauterine insemination. They demonstrated that AMH provided less intra-individual fluctuation than the AFC both within and between cycles.…”
Section: Discussionmentioning
confidence: 99%
“…van Disseldorp et al [19] compared the AFC with the AMH as to both their inter-cycle variability across four subsequent cycles and their stability across a full cycle in 77 women undergoing intrauterine insemination. They demonstrated that AMH provided less intra-individual fluctuation than the AFC both within and between cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Given that AMH represents the pool of oocytes remaining in the ovary, as a metric, it results in both consistent inter-and intra-menstrual cycle measurements [9]. Numerous studies have attempted to establish the efficacy of AMH in the fertility evaluation and treatment with measures of sensitivity, specificity, and predictive values.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of AMH determination was first proven in assisted reproduction, as AMH levels reflect the ovarian reserve potential with high accuracy (9)(10)(11)(12). There is also a strong correlation basal AMH level and the number of retrieved oocytes (10,12).…”
Section: Assisted Reproductionmentioning
confidence: 99%